Place-making, place-disruption, and place protection of urban blue spaces: perceptions of waterfront planning of a polluted urban waterbody. Issue 8 (3rd August 2021) - Toomey, A.H.; Campbell, L.K.; Johnson, M.; Strehlau-Howay, L.; Manzolillo, B.; Thomas, C.; Graham, T.; Palta, M.
ABSTRACT: Urban waterfronts are experiencing a renaissance, as it is estimated that by 2030 more than 60 percent of the world's population will live in cities, the majority of which are located in coastal or riparian regions. On a global level, changing public demands have spurred a new language of sustainability, revitalisation, and resilience with regard to urban waterfronts. Prior research has explored the potential ecological and social impacts of these trends, both in terms of benefits such as opportunities for recreation, as well as negative consequences such as increasing gentrification. Less explored, however, are how these planning and development processes can alternately support and/or interrupt existing "sense of place" that people hold with waterfront spaces, particularly spaces considered to be degraded and/or that are located in marginalised communities. This paper explores place-making, place-disruption and place protection associated with Coney Island Creek, a heavily polluted waterbody in New York City. We find that the creek provides recreation, sustenance, and social connections for substantial numbers of people, and we discuss these findings in the context of proposed resiliency planning and development projects that are perceived by some local stewards to threaten existing place attachments and meanings. In particular, we emphasise the importance of incorporating local knowledge and values in waterfront planning, especially in neighbourhoods that have been historically marginalised. This study contributes to a growing literature on values associated with urban blue spaces, thus furthering knowledge of how to improve current environmental governance strategies in coastal cities around the world.